The effects of dams on macroinvertebrates: Global trends and insights. (23rd April 2019) - Wang, Jun; Ding, Liuyong; Tao, Juan; Ding, Chengzhi; He, Daming
Abstract: Dams threaten a wide range of aquatic organisms in most rivers and are thus a primary cause of global biodiversity degradation. Although macroinvertebrates play important roles in biogeochemical processes and ecosystem structuring and functioning through food web links, a global overview of research on their responses to dam construction and the subsequent flow alteration is lacking. This study bibliometrically analysed publications with regard to dams and macroinvertebrates over the last 100 years (1920–2018). The results found that macroinvertebrates have been increasingly studied in regard to damming rivers globally during the research period. The United States contributed the most to the total publication output (21.14%). Keyword analysis revealed a clear evolution and distributional pattern of research themes and studied taxa. Studies on a single taxon were more common in early times, and recent studies have shifted to multiple taxa at the community level. Different countries/territories have different research priorities (i.e., themes and taxa). "Dam removal" and "restoration" occurred more frequently in American studies, and "river regulation" was highly researched in Australia and Poland. "Schistosomiasis" was a featured topic in China and Brazil. "Mollusc" was the top taxon of focus for America, China, and Brazil. The results also demonstrated that "functional diversity, " "model, " and "stable isotope" are emerging hotspots in this research area. Possible explanations and implications of the above findings are discussed. This study provides an integral understanding of the research on dams and macroinvertebrates, highlighting the potential conservation imbalance among countries/territories and taxa.